Identification and Characterization of a Cellodextrin Transporter in Aspergillus niger - Lin, Hui; Zhao, Jun; Zhang, Qingqing; Cui, Shixiu; Fan, Zhiliang; Chen, Hongge; Tian, Chaoguang (Frontiers in Microbiology, 2020)
Aspergillus niger produces a wide spectrum of extracellular polysaccharide hydrolases that hydrolyze cellulose into soluble glucose and cellodextrins. Transporters are essential for sugar uptake, yet it is not clear whether cellodextrin transporters exist in A. niger. Here, one cellulose inducible cellodextrin transporter CtA was identified in A. niger B2. It was found that CtA not only could transport cellobiose, but also cellotriose, cellotetraose, and cellopentaose. The yeast strain YPG-CtA, expressing cellodextrin transporter CtA and an intracellular -glucosidase, grew on cellobiose with the cell growth rate of 0.0830 ± 0.0113 h-1 under aerobic condition. Furthermore, the engineered yeast could produce 1.1 g/L ethanol anaerobically on cellobiose in 2 days. The identification of CtA provides evidence that the cellodextrin uptake is a complementary strategy of cellulose utilization in A. niger, and the CtA could be a strong transporter candidate for constructing engineered cellodextrin-utilizing microorganisms.